Differential pathways to higher education: A social justice analysis of international students from the Global South and refugees in Germany - Fernandes, Gabriela; Hernández-López, Elizabeth M. (Journal of International Students, 2026)
This study examines the differential experiences of international students from the Global South and refugees accessing higher education in Germany through Fraser’s (2008) tri-dimensional framework of social justice: redistribution, recognition, and representation. While both groups share overlapping challenges in navigating German higher education, existing research has largely treated them separately, creating gaps in understanding their comparative experiences and support needs. Using a conceptual qualitative research design informed by theory synthesis, the study finds that Global South students face economic barriers and cultural misrecognition despite educational legitimacy, while refugees encounter compounded obstacles, including legal uncertainties and recognition deficits, even with targeted support programs. Both experience compound injustice, intersecting economic, cultural, and political exclusion. The analysis reveals that current support systems operate on homogenizing principles, failing to reflect the intersectional realities of these students. Institutional reform grounded in social justice is urgently needed to foster genuinely inclusive educational environments